The prophet story courseware - Saya Sayang Rasul (SSR) / Nor Azila Awang Abu Bakar, Nur Mimi Adila Ismail and Nazatul Azleen Zainal Abidin - Awang Abu Bakar, Nor Azila; Adila Ismail, Nur Mimi; Zainal Abidin, Nazatul Azleen (2015)
This paper aims to highlight the development of a multimedia courseware entitled Saya Sayang Rasul (SSR) to serve as a reference tool for level 2 Malaysian primary school students to learn about the Sirah topic in Pendidikan Islam subject. Currently, the textbook, reference books or notes taken from the Internet are the main sources of reference to study Sirah. Although there are many efforts in accompanying the text with attractive colourful pictures, interactive animations is said to capture the attention of the students more. The multimedia elements such as graphic, animation, text, audio and video are manipulated to present the information in a more interactive way so that the student get better understanding and help them to memorize the important information regarding the history of our beloved prophet. This courseware is developed based on ADDIE Model which comprises of Analysis, Design, Development, Implementation and Evaluation phases. Another two phases are added which are Preliminary Study and Documentation to complete the project. The evaluation of the Courseware was conducted on 30 respondents and to three experts. Questionnaire was used as an instrument to collect data. Results from the analysis indicate that the courseware had satisfied the respondents in terms of user interface (mean = 4.47), usability (mean = 4.53) and content (mean = 4.70) of the courseware. The dispersion of standard deviation is also small (< 1) for all categories thus implies there's only insignificant difference in the respondents' satisfactory level.